SMART-KMP Framework: Model Smart Cooperative Berbasis Sistem Informasi dan Artifical Intelligence pada Koperasi Merah Putih - Agus Nugraha (LPPM Universitas Koperasi Indonesia, 2026)
Digital transformation has become a strategic necessity for cooperatives to enhance operational efficiency, service quality, governance transparency, and organizational competitiveness in the digital economy era. The Red and White Village/Sub-district Cooperative (Koperasi Desa/Kelurahan Merah Putih, KD/KMP) program initiated by the Government of Indonesia encourages cooperatives to adopt digital technologies in a more integrated manner. However, the implementation of digital transformation in cooperatives continues to face significant challenges, particularly the lack of integration among cooperative information systems, Artificial Intelligence (AI), cooperative governance, and the digital ecosystem within a comprehensive conceptual framework. This study aims to develop the SMART-KMP Framework as a conceptual design artifact to support the digital transformation of the Red and White Cooperative. The study employs the Design Science Research (DSR) methodology, comprising problem identification, Systematic Literature Review, Research Gap Analysis, Requirement Analysis, Framework Design, and Expert Validation. The research results in the SMART-KMP Framework, which consists of four integrated layers: Digital Cooperative Core, Artificial Intelligence Layer, Governance and Knowledge Management Layer, and Collaborative Digital Ecosystem. The framework integrates cooperative business processes, AI-driven data-based decision-making, good cooperative governance practices, and digital collaboration among government institutions, financial institutions, marketplaces, suppliers, MSMEs, and other stakeholders. This study contributes by proposing a conceptual model that enriches the Smart Cooperative literature while providing a reference framework for the development of cooperative information systems, the formulation of digital transformation policies, and the implementation of the Red and White Cooperative program in Indonesia.